(untitled) (UCC Law Journal, 2025)
This paper examines the doctrine of informed consent within the Ghanaian healthcare system, interrogating the significant disconnect between its progressive enactment and the practical realities of its implementation. The claim made in the paper is that the complex legal doctrine of informed consent, when transplanted into Ghana’s healthcare system, reflects modern patient-centric standards from advanced jurisdictions, yet remains largely theoretical in Ghana. This shortfall is evidenced by a complete absence of judicial precedents and direct jurisprudence on informed consent, amid persistent systemic and socio–cultural barriers. Using a doctrinal research methodology coupled with a socio-legal contextual analysis, this paper analyses primary and secondary legal sources to establish the challenges encountered in implementing the doctrine of informed consent. Although informed consent, as outlined in Ghanaian law, reflects the context in which it has been used and applied in advanced countries, systemic challenges, evidenced by recent data on literacy rates and inadequate doctor-to-patient ratios, are identified as hurdles that render the practical application of the doctrine of informed consent largely aspirational. Ghana’s doctor-to-patient ratio falls below the World Health Organisation recommended ratio of 1:1,320. The paper concludes that for informed consent to transition from rhetoric to reality in Ghana, a modified framework of contextualised informed consent is required. This paper proposes measures such as the development of standardised consent protocols for low-literacy populations, the formulation of official guidelines for navigating familial involvement in decision-making, and the introduction of comprehensive language policies in the training of health professionals and medical interpreters.